Cooperative Learning Method through Animal Food Board Demonstration for Improving Student Learning Outcomes in Natural Science Lessons - Hikmah Agustin (International Journal of Educational Qualitative Quantitative Research, 2022)
Improving student learning outcomes is one of the goals of education. This study aimed to determine the effect of cooperative learning through animal food board demonstration for improving student learning outcomes in learning Natural Sciences (IPA) for class 4 MI Salafiyah Cirebon City, West Java, Indonesia. The approach used in this research is quantitative, while the method used is the pre-experimental method with the research design used is one group pre-test post-test design. The population in this study were all 4th-grade students of MI Salafiyyah Cirebon City. The sample of this study was 25 students. Data were collected through a test where there was a pre-test and post-test. Data were analyzed through statistical descriptive, normality, homogeneity, and Mann-Whitney statistical tests using SPSS version 16 for windows. Based on the study results, the pre-test score was 65.60, and the post-test score was 90.20. Based on the results of the Mann-Whitney test with = 0.05, a significance value of 0.000 was obtained. The results obtained were 0.000 <0.05 indicating a significant difference, there was a significant effect on the difference in the treatment applied, in other words, an increase in student learning outcomes by applying the Cooperative learning model by using animal food board demonstration of educative teaching aids in science subjects (Natural Sciences/IPA) significantly.